The fishing gears using in Kemaliye Region of Keban Dam Lake - Duman, Erdal; Karlıdağ, Yelda (Ege Üniversitesi, 2017)
This study was aimed to determine the structures of fishing gears used in the Kemaliye Region of Keban Dam Lake between July 2012- June 2013. In  study area were gone one day a week, measurements were made as a result of observations on the structural characteristics of fishing gears, fishing boats and fishermen's fishing season, where they kept the nets. In the present study, it was found that the most of fishing gears used in this region (2000 hectare) were  gillnets (14000 m) . In addition, trammel nets and crayfish traps were also used. During this study, it was determined that total 12200 m of its were monofilament and 1800 m of its were multifilament. Total 900 m trammel nets were also determined. In addition, total 1500 traps used for crayfish catching were examined.

Bu çalışma Temmuz 2012 - Haziran 2013 tarihleri arasında Keban Baraj Gölü Kemaliye Bölgesi’nde kullanılan av araçlarının yapısını incelemek amacı ile yapıldı. Çalışma bölgesine haftada bir gün gidildi, av araçlarının yapısal özellikleri, tekne üzerinde ve balıkçıların avlama sezonu dışında ağları muhafaza ettikleri yerlerde yapılan ölçümler, gözlemler sonucunda saptandı. Bu araştırmada Kemaliye Bölgesinde kullanılan av araçlarının çoğunluğunu monofilament sade ağların oluşturduğu belirlendi. Ayrıca fanyalı ağlar ve kerevit avcılığında da pinterin kullanıldığı görüldü. Çalışma süresince, Keban Baraj Gölü Kemaliye Bölgesinde (2000 hektar) toplam 14000 m uzunluğunda sade ağ incelenmiş olup, bunun 12200 m’si monofilament sade ağlar, 1800 m’si de multifilament sade ağlardan oluştuğu saptandı. Toplam 900 m uzunluğunda fanyalı ağ da tespit edildi. Kerevit avcılığında ise kullanılan toplam 1500 adet kerevit pinteri incelendi.
Keban Baraj Gölü Kemaliye Bölgesi’nde kullanılan av araçları